ANALISIS DETERMINAN KEPUASAN KONSUMEN PADA LAYANAN FOOD DELIVERY DILINGKUNGAN AKADEMIS : SUDI EMPIRIK PENGGUNA GOFOOD - Marhaeni Widiastuti, Tri; Agustiningtyas, Eka; Setiyowati, Ari Ika; Aprilia, Alfinda Dewi (JOURNAL AKSES STIA MALANG, 2026)
The rapid development of information technology has transformed consumer behavior, particularly in the digital food delivery sector. This study aims to examine and analyze the effect of GoFood service quality on customer satisfaction among undergraduate students at the Malang School of Administrative Sciences (STIA). Using a quantitative approach, data were collected through questionnaires from 70 respondents selected using a purposive sampling technique. Data analysis was performed using simple linear regression, classical assumption tests, and hypothesis testing (t-tests). The results demonstrate that service quality has a positive and significant effect on customer satisfaction, with a coefficient of determination (R2) of 0.440. This indicates that 44% of the variation in customer satisfaction is explained by service quality, while the remainder is influenced by factors outside this research model.